PP55 Influence of microencapsulation on the stability and evaluation of the antimicrobial activity of essential oils from the Lamiaceae family - patino, william; Garzon Restrepo, Sintia Juliet (Revista Productos Naturales, 2025)
Skin infections, such as acne, are a common reason for dermatological consultations and are associated with pathogens like Staphylococcus aureus and Propionibacterium acnes. Although antimicrobials are used, bacterial resistance has spurred the search for alternatives, such as essential oils (EO), whose bioactive compounds possess antiseptic properties. However, their volatility limits their application, which is why microencapsulation emerges as a strategy to improve their stability. This study prioritized four plant species rich in monoterpenes and evaluated three microencapsulation methods. Both free and encapsulated EO demonstrated antibacterial activity, highlighting their potential in dermatological formulations.
Keywords: essential oils; microencapsulation; antimicrobial activity